Molecular basis of intramolecular electron transfer in proteins during radical-mediated oxidations: Computer simulation studies in model tyrosine-cysteine peptides in solution - Petruk, Ariel Alcides (2012)
Experimental studies in hemeproteins and model Tyr/Cys-containing peptides exposed to oxidizing and nitrating species suggest that intramolecular electron transfer (IET) between tyrosyl radicals (Tyr-O) and Cys residues controls oxidative modification yields. The molecular basis of this IET process is not sufficiently understood with structural atomic detail. Herein, we analyzed using molecular dynamics and quantum mechanics-based computational calculations, mechanistic possibilities for the radical transfer reaction in Tyr/Cys-containing peptides in solution and correlated them with existing experimental data. Our results support that Tyr-O to Cys radical transfer is mediated by an acid/base equilibrium that involves deprotonation of Cys to form the thiolate, followed by a likely rate-limiting transfer process to yield cysteinyl radical and a Tyr phenolate; proton uptake by Tyr completes the reaction. Both, the pKa values of the Tyr phenol and Cys thiol groups and the energetic and kinetics of the reversible IET are revealed as key physico-chemical factors. The proposed mechanism constitutes a case of sequential, acid/base equilibrium-dependent and solvent-mediated, proton-coupled electron transfer and explains the dependency of oxidative yields in Tyr/Cys peptides as a function of the number of alanine spacers. These findings contribute to explain oxidative modifications in proteins that contain sequence and/or spatially close Tyr-Cys residues. © 2012 Elsevier Inc. All rights reserved.